Estrategia de desarrollo para la innovación de la Feria del Agricultor de la Municipalidad de San Carlos - Víquez-Rojas, Karolay (Instituto Tecnológico de Costa Rica, 2019)
The main objective of this project is to propose a development plan applied to the Ciudad Quesada Farmer's Fair, which consists in determining and analyzing the current position of the fair, based on this, determining both positive and negative aspects, and then create strategies that contribute to the improvement of the farmer's fair and guide their actions over the next 5 years. The project has a qualitative approach, in addition to a descriptive scope, since it observes and defines the environment in which it is presented without influencing it and has a transversal temporality, because the data is in a single moment in time. In the same way, the results, conclusions and recommendations of said strategic plan are presented, which shows that the Ciudad Quesada Farmers Fair has an average position in terms of competitive advantage, since in some aspects it is well, but in others it must improve. It also shows the strategies proposed to improve the fair, which are aimed at making the fair more aware of the environment and that greener, to improve the information and communication of the fair with people, increase fair sales, attract to more vendors that meet the needs and train farmers on different topics. Finally, the proposed development plan is easy to implement and carry out, because most of the strategies consist of taking advantage of the current resources of the fair and very few require financial resources or different from those of the organization.
Proyecto de investigación (Bachiller en Administración de Empresas). Instituto Tecnológico de Costa Rica, Escuela de Administración de Empresas,2019
Keywords: Innovaciones; Pequeños agricultores; Administración de empresas; Productores artesanales; Research Subject Categories::SOCIAL SCIENCES::Business and economics::Business studies